The impact of blended learning on students' motivation towards learning and social studies teachers' attitudes towards it in Al-Sharqiyah South Governorate in the Sultanate of Oman - Al-Majali, Aisha Abdullah Muhammad; Al-Masrouri, Fahd Salem Saif (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed to reveal the impact of blended learning on students' motivation towards learning in the Al Sharqiyah South Governorate in the Sultanate of Oman, in addition to determining the impact of the variables of gender and educational stage. Oman, in addition to determining the impact of the variables of gender, teaching experience, specialization, and academic qualification. To achieve the objectives of the study, the researchers used the descriptive approach, where the researchers prepared a questionnaire for students' motivation towards blended learning, which consisted of (15) statements, while the second questionnaire concerned the attitudes of social studies teachers towards blended learning, consisted of (13) statements, and after verifying the validity and stability of the tool. It was applied to the study sample consisting of (100) male and female students from basic and post-basic education schools in Al Sharqiyah South Governorate, and (26) male and female teachers. The results of the study showed that the motivation of female students towards blended learning in the Al Sharqiyah South Governorate in the Sultanate of Oman amounted to (3.93), that is, with a high degree. The results also showed that there were statistically significant differences at the significance level (α = 0.05) in the students’ scale due to the gender variable in favor of males. The results also revealed that there were no statistically significant differences at the significance level (α = 0.05) in the students' scale due to the grade variable. The results of the study revealed that the attitudes of male and female social studies teachers towards blended learning amounted to (4.06), that is, with a high degree. The results also showed that there were no statistically significant differences at the significance level (α = 0.05) due to all variables, gender, years of experience, educational qualification, and specialization. The study recommends employing blended learning in addition to direct education in the tenth and eleventh grades and conducting training courses to train teachers on how to teach the values of citizenship.
Keywords: blended learning; motivation; social studies; trends